MORPHO-PHYSIOLOGICAL DISSECTION OF HEAT TOLERANCE IN CERTAIN POOL OF SOYBEAN GENOTYPES - SARWAR, S; HASSAN, M; ZAFAR, SA; ATIF, M; RASOOL, MG; KHAN, AR; HASSAN, A; ALTAF, M (Biological and Clinical Sciences Research Journal, 2024)
Under the scenario of climate change, crop diversification through the incorporation of non-conventional oilseed crops like soybean in the cropping pattern is a need of the time. However, being native to regions having mild temperatures, soybean faces difficulty in adaptation in areas of lower latitude with high temperatures and short day lengths during growing periods. This situation directs the researchers to determine the tolerance of soybean genotypes against high temperatures and to establish a selection criterion for the identification of adaptable traits. For this purpose, a study was conducted at Oilseeds Research Institute, Faisalabad. Forty soybean genotypes including approved varieties were screened for tolerance against high temperatures in the growth chamber and glass house. At the seedling stage, genotypes were categorized into tolerant, moderately tolerant, and susceptible categories based on their STI values in the growth chamber and values of certain morpho-physiological parameters in a glass house. Considering the seed yield an ultimate goal in the adaptation process, its study is crucial in field conditions. Tolerant and moderately tolerant genotypes from previous experiments were sown in the field. Data of yield and contributing traits were recorded at maturity and subjected to analysis. Results showed great variability among genotypes for all the traits. AARI Soybean gave the best yield followed by Faisal Soybean, ORI-SOY-91, and ORI-SOY-102. All of these genotypes/varieties also performed well in terms of electrolyte leakage and leaf-relative water content. To conclude, these varieties would show better adaptation in high-temperature areas. Moreover, both the varieties along with 2 best-performing genotypes may prove to be better parents in future hybridization programs.